2011
DOI: 10.1021/ja201581x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition of Insulin by a Synthetic Receptor

Abstract: The discovery of molecules that bind tightly and selectively to desired proteins continues to drive innovation at the interface of chemistry and biology. This paper describes the binding of human insulin by the synthetic receptor cucurbit[7]uril (Q7) in vitro. Isothermal titration calorimetry and fluorescence spectroscopy experiments show that Q7 binds to insulin with an equilibrium association constant of 1.5 × 106 M-1 and with 50-100-fold selectivity versus proteins that are much larger but lack an N-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
416
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 296 publications
(432 citation statements)
references
References 37 publications
8
416
0
3
Order By: Relevance
“…Recently our group has shown that this selectivity can translate from peptides to folded proteins via the unraveling of the terminus to accommodate Q7. 6 Despite the excellent selectivity observed in these systems, the lowest Kd values (for N-terminal phenylalanine) are in the 0.1-1 M range. Such affinities by artificial receptors in aqueous solution are considered relatively high by current standards in the field, 7 but a 100-fold or better boost in affinity would significantly increase the viability of in vivo applications.…”
Section: Introductionmentioning
confidence: 97%
“…Recently our group has shown that this selectivity can translate from peptides to folded proteins via the unraveling of the terminus to accommodate Q7. 6 Despite the excellent selectivity observed in these systems, the lowest Kd values (for N-terminal phenylalanine) are in the 0.1-1 M range. Such affinities by artificial receptors in aqueous solution are considered relatively high by current standards in the field, 7 but a 100-fold or better boost in affinity would significantly increase the viability of in vivo applications.…”
Section: Introductionmentioning
confidence: 97%
“…By contrast, no such difference in binding affinity was observed with the N‐terminal acetylated peptide (Ac‐FGG‐ERα) upon the addition of Q8 (Figure 2 C). Furthermore, the analogous cucurbit[7]uril, Q7, which binds only one FGG moiety,30 did not enhance the apparent affinity of FGG‐ERα for the 14‐3‐3 protein (Figure 2 E). Combined, these reference experiments provide experimental evidence that the enhancement of the apparent affinity between the FGG‐ERα peptide cargo and 14‐3‐3 protein by Q8 relies exclusively on its postulated bivalent FGG recognition.…”
mentioning
confidence: 95%
“…[6][7][8] We and others have studied the capacity of Q7 to bind to amino acids, peptides, and proteins and found that Q7 prefers to bind Nterminal phenylalanine (Phe), tyrosine (Tyr), and tryptophan (Trp) residues, by incorporating the sidechain within the nonpolar Q7 cavity and chelating the N-terminal ammonium group with Q7 carbonyl oxygens. [9][10][11][12][13][14] Nau and coworkers have shown that Q7 can slow the activity of an endopeptidase, trypsin, and an exopeptidase, leucine aminopeptidase (LAP), by binding to their respective substrates. 15,16 In both cases, they observed only partial and short-lived inhibition.…”
Section: Introductionmentioning
confidence: 99%